Defining, assessing, and developing creativity in sport: a systematic narrative review - de Sa Fardilha, F.; Allen, J. B. (International Review of Sport and Exercise Psychology, 2020)
Research on creativity in sport is gaining momentum, due to a growing interest from coaches and academics in developing strategies to increase unpredictability in individual and collective behaviour which may allow teams to gain an important advantage over their opponents. The purpose of this paper was to conduct the first systematic narrative review of the literature on sporting creativity, critically synthesising 51 years of published research (1967-2018) and proposing avenues for future research. Six databases were used, and 48 documents met search criteria. The findings are organised in four categories: (a) defining creativity, (b) correlates of creativity, (c) assessing creativity and (d) developing creativity. Creativity definitions and assessments have privileged thought processes over the ability to act. A distinction is warranted between creativity about sport and creativity in sport (in action) and aligned assessment methods. The literature does not support a single strategy for the development of sporting creativity but does support its trainability. Evidence of the effectiveness of programmes for the enhancement of sporting creativity is growing but is still limited. Furthermore, while it is recognised that coaches have a pivotal role in the development of sporting creativity, research involving them is still scarce.